2015
DOI: 10.1007/s00213-015-3945-7
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol effects in the prepulse inhibition disruption induced by amphetamine

Abstract: These results corroborate findings indicating that CBD induces antipsychotic-like effects. In addition, they pointed to the nucleus accumbens as a possible site of these effects. The increase of anandamide availability may be enrolled in the CBD effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
2
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 60 publications
1
36
2
13
Order By: Relevance
“…A second potential target for CBD is the FAAH enzyme which is located intracellularly (Leweke et al, 2012;Pedrazzi et al, 2015). In the case of URB597, there is in vitro evidence to suggest that it can penetrate the plasma membrane to directly inhibit FAAH, albeit in a pH-sensitive manner (Paylor et al, 2006).…”
Section: Potential Mechanisms Of Antipsychotic Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…A second potential target for CBD is the FAAH enzyme which is located intracellularly (Leweke et al, 2012;Pedrazzi et al, 2015). In the case of URB597, there is in vitro evidence to suggest that it can penetrate the plasma membrane to directly inhibit FAAH, albeit in a pH-sensitive manner (Paylor et al, 2006).…”
Section: Potential Mechanisms Of Antipsychotic Effectmentioning
confidence: 99%
“…Recent work has shown in Swiss mice that intra-accumbal administration of CBD (60 nmol) inhibited disruption of PPI induced by systemic injections of amphetamine (10 mg/kg) (Pedrazzi et al, 2015). This study also reported that a systemic injection of the FAAH inhibitor, URB597 (0.3-1 mg/kg), was able to inhibit amphetamine-induced disruption of PPI and this was indirect evidence in support of the role of CBD as an inhibitor of AEA reuptake.…”
Section: Speciesmentioning
confidence: 99%
“…In male Swiss mice, cannabidiol (15, 30, or 60 mg/kg) did not affect PPI or startle amplitude (Pedrazzi et al, 2015). On the other hand, Long et al (2006) reported that C57BL/6JArc mice acutely treated with cannabidiol (1 and 15, but not 5 mg/kg) showed increased startle amplitudes while PPI remained unaffected.…”
Section: Antipsychotic Potential Of Cannabidiol: Insights From Preclimentioning
confidence: 99%
“…While the precise neuroanatomical regions responsible for CBD's actions are not known, considerable evidence implicates the nucleus accumbens (NAc) as an important site for CBD's modulatory effects on various cognitive and behavioral phenomena (Guimarães et al, 2004;Bhattacharyya et al, 2009;Valvassori et al, 2011;Mijangos-Moreno et al, 2014;Pedrazzi et al, 2015). For example, CBD attenuates THCinduced dysregulation of the ventral striatum during verbal recall tasks (Bhattacharyya et al, 2009) and increases c-fos and adenosine levels in rodent NAc (Guimarães et al, 2004;Mijangos-Moreno et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, CBD attenuates THCinduced dysregulation of the ventral striatum during verbal recall tasks (Bhattacharyya et al, 2009) and increases c-fos and adenosine levels in rodent NAc (Guimarães et al, 2004;Mijangos-Moreno et al, 2014). In addition, CBD blocks amphetamine-induced oxidative stress in the NAc (Valvassori et al, 2011) and intra-NAc CBD attenuates amphetamineinduced deficits in prepulse inhibition (Pedrazzi et al, 2015;Renard et al, 2016b). Nevertheless, the precise functional and pharmacological mechanisms by which CBD may produce these effects in the mesolimbic system are not currently understood.…”
Section: Introductionmentioning
confidence: 99%